Memorandum of Understanding between the BRAC University (BRACU) Centre for Languages (CfL) and Open University Worldwide Limited (2009) - BRAC University; Open University Worldwide Limited (BRAC University and Open University Worldwide Limited, 2013)
This Memorandum of Understanding ("MoU") is made this 25th day of May 2009, between BRAC University ("BRACU") Centre for Languages (CfL), 66 Mohakhali, Dhaka, Bangladesh and Open University Worldwide Limited (a limited company registered under the laws of England and Wales with registration number 1260275) whose registered office is at Walton Hall, Milton Keynes, MK7 6AA, United Kingdom ("OUW").